IMPLEMENTASI AUGMENTED REALITY TERHADAP TUJUH KEAJAIBAN DUNIA MENGGUNAKAN METODE MARKER BASED TRACKING (MBT) BERBASIS ANDROID - Yesy Afrillia; Dasril Dasril (LPPM Politeknik LP3I Medan, 2021)
The wonder of the world is cultural wisdom placed in the form of a list of the most important man-made creations. The seven wonders of the world are extraordinary masterpieces that make people think that beauty seems impossible to make in its time. With the advancement of multimedia technology, it needs to be developed into a learning medium about the introduction of the seven wonders of the world 3D using Augmented Reality (AR) technology. Augmented Reality (AR) technology is a technology that combines a two- or three-dimensional virtual object into a real three-dimensional environment and then projects those virtual objects into real time. This research aims to attract students who want to see more real how the original form of the monument of the seven wonders of the world. The design uses sketchup software for object creation, Vuforia Augmented Reality app to create android apps and Unity app to process images, sounds, and graphics. The development of this application uses augmented reality technology with Marker Based Tracking method. This method will track marker patterns that have been saved to display digital elements. The ideal distance for marker detection is 20 -90 cm with an angle slope between 0o - 90o.